The European Union’s R&D potential after Brexit – Opportunities and Threats - Anna ODROBINA; Katarzyna STABRYLA-CHUDZIO (Communications of International Proceedings, 2020)
Brexit poses a great challenge to the EU, whose R&D potential will be significantly weakened. In general terms, this would mean a downturn in EU research and development, considering the necessity of gaining some distance on the USA and East Asia. In the paper, the authors attempt to identify opportunities and threats to the development of R&D in the EU after Brexit. The study also aims to establish the impact of the UK on the EU in the area of R&D and the importance of the EU in the global economy as well as determining opportunities for the development of R&D potential after Brexit and possible threats arising from this process. It seems necessary to specify postulates regarding actions to avoid negative effects on the R&D potential of the EU. Therefore, directions and areas of desirable actions will be developed for strengthening EU R&D, especially in the aspect of shaping the EU’s innovation policy.
Keywords: Research and development; EU industrial R&D; EU innovation policy; EU funds; Brexit; global system of R&D.